Charmonium suppression in ultra-relativistic proton–proton collisions at LHC energies: a hint for QGP in small systems - Captain R. Singh; Suman Deb; Raghunath Sahoo; Jan-e Alam (European Physical Journal C: Particles and Fields, 2022)
Abstract Proton–proton (pp) collision has been considered as a baseline to study the system produced in relativistic heavy-ion (AA) collisions with the basic assumption that no thermal medium is formed in pp collisions. This warrants a cautious analysis of the system produced in pp collisions at relativistic energies. In this work we investigate the charmonium suppression in pp collisions at $$\sqrt{s} = 5.02$$ s = 5.02 , 7 and 13 TeV energies. Further, charmonium suppression has been studied for various event multiplicities and transverse momenta by including the mechanisms of color screening, gluonic dissociation, collisional damping along with regeneration due to correlated $$c{\bar{c}}$$ c c ¯ pairs. Here we obtain a net suppression of charmonia at high-multiplicity events indicating the possibility of the formation of quark–gluon plasma in pp collisions.